Impact of foreign direct investment on economic growth: The role of financial development in the context of developing economies - Guan, Thew Kim (Asian Journal of Economics and Empirical Research, 2024)
According to economic theory, foreign direct investment inflows (hereafter “FDI”) are a crucial catalyst for stimulating economic growth, as FDI has the capacity to attract technology, leading to a subsequent rise in economic growth (hereafter “EGT”). Scholars continue to debate the convincing clarification of the direct impact of FDI on economic growth (thereafter “EGT”), despite the frequent emphasis on the absorptive capacity of host nations. This uncertainty may arise from neglecting the influence of specific conditioning factors. This study aims to examine the empirical relationship between FDI and EGT in the case of seventy developing nations during 1990-2023. Additionally, the study seeks to evaluate whether the impact of FDI on EGT varies according to the level of financial development. This paper specifically addresses the endogeneity problem by employing the General Methods of Moments (GMM) to estimate the instrumental variable approach. The empirical investigation reveals that there exists a specific level of financial development (hereafter “FND”), known as a threshold, at which FDI begins to positively affect EGT. Conversely, below this threshold, FDI has a detrimental effect on EGT. Policymakers in emerging nations should consider the level of domestic financial development to benefit from increasing foreign investment.